2000
DOI: 10.1016/s1359-6454(00)00064-1
|View full text |Cite
|
Sign up to set email alerts
|

HRTEM study of Co7W6 and its typical defect structure

Abstract: AbstractÐThe tetrahedrally close-packed structure of Co 7 W 6 (m-phase) was studied by HRTEM. A massive presence of random sub-unit cell twins was detected. These planar defects were characterized in detail and the twinning probability at potential mirror planes was established. High-precision image simulation of the bulk structure and defect region was performed, using a simulated evolution optimization strategy to re®ne the imaging conditions. Ab initio calculations were carried out in order to determine the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
38
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 29 publications
4
38
0
Order By: Relevance
“…The formation of a μ-phase was confirmed in a few binary alloys such as Co-W [19], Co-Mo [20], Fe-W [20]and Fe-Mo [21] alloys, as well as in some Ni-based B 7 A 6 -type superalloys [15,22,23] such as Co 7 W 6 , Co 7 Mo 6 , and Fe 7 W 6 . The structure of the μ-phase belongs to the D 5 3d −R 3m space group, with a = 0.476 nm and c = 2.56 nm [22].…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…The formation of a μ-phase was confirmed in a few binary alloys such as Co-W [19], Co-Mo [20], Fe-W [20]and Fe-Mo [21] alloys, as well as in some Ni-based B 7 A 6 -type superalloys [15,22,23] such as Co 7 W 6 , Co 7 Mo 6 , and Fe 7 W 6 . The structure of the μ-phase belongs to the D 5 3d −R 3m space group, with a = 0.476 nm and c = 2.56 nm [22].…”
Section: Introductionmentioning
confidence: 85%
“…So both γ′-phase and γ-matrix would have same orientation relationship with μ-phase. The selected area diffraction patterns for needle-type μ-phase suggested that the needle-type μ-phase had the relationship (104) μ || (100) γ/γ′ and [4 19 1] μ || [0 1 1] γ/γ′ with γ′-phase and γ-matrix, while the blocky μ-phase had the relationship [12 2 − 1] μ || [0 0 1] γ/γ′ but about 14.7°between (1 − 1 10) μ and (100) γ/γ′ as shown in Fig. 11(d) and Fig.…”
Section: Growth Orientation Of the μ-Phasementioning
confidence: 99%
“…The m phase precipitation behavior has been extensively studied in superalloys during the past decades [4,[14][15][16][17][18]. Many kinds of structural defects such as stacking faults, twin bands, microtwins, and intergrowth in m phase were found in superalloys or intermetallics [14][15][16][19][20][21]. In addition, the P phase was involved in some previous work [2,12,19,22].…”
mentioning
confidence: 99%
“…D0 19 Co 3 W transformation and a description of the defect formation mechanisms can be found elsewhere (Carvalho et al 2000). The chemical contrast in Co 3 W images can be assessed from ®gure 3.…”
mentioning
confidence: 99%
“…To the best of our knowledge, these partly intrinsic and partly extrinsic superlattice defects have not been identi®ed before in D0 19 phases. The crystallographic changes produced in the D0 19 structure can most easily be described by a p-rotation around [0001] (Carvalho et al 2000) and for this reason such defects have been called p rotation faults (pRFs). The diOE erence in atomic arrangement between the SISF (f SISFˆ1 3 ‰ · 1 1100Š) and the pRF (f pRFˆ1 6 ‰ · 2 2203Š), when viewed along ‰11 · 2 20Š, can be evaluated in ®gure 6.…”
mentioning
confidence: 99%